Immune-Inflammatory Responses of an Acellular Cartilage Matrix Biomimetic Scaffold in a Xenotransplantation Goat Model for Cartilage Tissue Engineering - Jia, Litao; Zhang, Peiling; Ci, Zheng; Zhang, Wei; Liu, Yu; Jiang, Haiyue; Zhou, Guangdong (Frontiers in Bioengineering and Biotechnology, 2021)
The rapid development of tissue engineering and regenerative medicine has introduced a new strategy for ear reconstruction, successfully regenerating human-ear-shaped cartilage and achieving the first clinical breakthrough using a polyglycolic acid/polylactic acid (PGA/PLA) scaffold. However, its clinical repair varies greatly among individuals, and the quality of regenerated cartilage is unstable, which seriously limits further clinical application. Acellular cartilage matrix (ACM), with a cartilage-specific microenvironment, good biocompatibility, and potential to promote cell proliferation, has been used to regenerate homogeneous ear-shaped cartilage in immunocompromised nude mice. However, there is no evidence on whether ACM will regenerate homogeneous cartilage tissue in large animals or has the potential for clinical transformation. In this study, xenogeneic ACM assisted with gelatin (GT) with or without autologous chondrocytes was implanted subcutaneously into goats to establish a xenotransplantation model and compared with a PGA/PLA scaffold to evaluate the immune-inflammatory response and quality of regenerated cartilage. The results confirmed the superiority of the ACM/GT, which has the potential capacity to promote cell proliferation and cartilage formation. Although there is a slight immune-inflammatory response in large animals, it does not affect the quality of the regenerated cartilage and forms homogeneous and mature cartilage. The current study provides detailed insights into the immune-inflammatory response of the xenogeneic ACM/GT and also provides scientific evidence for future clinical application of ACM/GT in cartilage tissue engineering.